Language and reality: the logical analysisin Russell, Wittgenstein and Carnap - Cadavid Ramírez, Lina Marcela; Ríos Restrepo, Leidy Andrea (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This article draws a relationship between three of the most influential authors of the doctrine of logical atomism from the notion of logical analysis, however, this relationship seeks not only the verification of its doctrinal closeness but the ontological conception that underlies the possibility of this analysis, in the case of Russell and Wittgenstein or his absence, in the case of Carnap, which, however, does not take him away from concerns of a metaphysical nature, since in all three the relationship between language and world, whether from the ontological or epistemological dimension involves a reflection of the first order. To expose the above it is necessary to elucidate the relationship between proper names and facts (Russell), simple objects and state of things (Wittgenstein) and the position of Unified Science (Carnap) with respect to the representation of facts or things.
Keywords: logical positivism; proper names; simple objects; unified science; facts